Quality of life, binge eating and sexual function in participants treated for obesity with sustained release naltrexone/bupropion. (23rd February 2018) - Halseth, A.; Shan, K.; Gilder, K.; Malone, M.; Acevedo, L.; Fujioka, K.
Summary: Objective: This multicenter, randomized, controlled, open‐label trial examined weight‐related quality of life, control over eating behaviour and sexual function after 26 weeks of treatment with either 32 mg naltrexone sustained release (SR)/360 mg bupropion SR plus a comprehensive lifestyle intervention program (NB + CLI, N  = 153) or usual care (UC, N  = 89), which included minimal lifestyle intervention. Methods: Impact of Weight on Quality of Life‐Lite, Binge Eating Scale and Arizona Sexual Experiences Scale were assessed at baseline (BL) and weeks 16 and 26. Results: NB + CLI and UC participants lost 9.46 and 0.94% respectively of initial body weight at week 26 ( P  < 0.0001). NB + CLI participants had greater improvements in Impact of Weight on Quality of Life‐Lite total score than UC participants ( P  < 0.0001). In participants with moderate/severe Binge Eating Scale scores at BL, 91% of NB + CLI and 18% of UC participants experienced categorical improvements. In participants with Arizona Sexual Experiences Scale‐defined sexual dysfunction at BL, 58% of NB + CLI and 19% of UC participants no longer met dysfunction criteria at week 26. The most frequent adverse events leading to discontinuation before week 26 in NB + CLI included nausea (10.5%); anxiety (3.3%); and headache, hypertension, insomnia and palpitations (1.3% each). Conclusion: Compared with UC, participants treated with NB + CLI experienced greater improvements in weight‐related quality of life, control over eating behaviour, and sexual function.